Regulatory Reform on Doctor Protection as an Effort to Prevent the Criminalization of Medical Actions - Emirza Nur Wicaksono (SEAN Institute, 2026)
The criminalization of medical actions is a crucial issue in the health law system that has direct implications for legal certainty for doctors and the protection of patients’ rights. This study aims to analyze the configuration of regulatory frameworks for doctor protection in Indonesia, identify legal factors that contribute to the criminalization of medical actions, assess the effectiveness of existing regulations, and formulate an ideal and proportional model of regulatory reform. This research employs a normative (doctrinal) legal research method with statutory and conceptual approaches, through analysis of laws and regulations, legal doctrines, and academic literature related to health law and medical criminal liability. The findings indicate that existing regulations have not yet provided optimal legal protection for doctors due to normative disharmony, unclear boundaries of medical malpractice, and weak integration of professional medical standards within criminal proceedings. This study proposes a regulatory reform model that emphasizes a tiered dispute resolution mechanism, strengthening the role of professional judgment, and limiting criminalization to medical errors that are clearly and demonstrably proven. These findings are expected to contribute to the development of health law theory and serve as a reference for policymakers in building a fair, proportional, and justice-oriented legal system in healthcare services.